Spirituality in the workplace: the role of 'Taqwa' towards the advancement of the contemporary organization - Kamil, Naail Mohammed; Sulaiman, Mohamed; Osman-Gani, Aahad M.; Mohd. Israil, Khaliq Ahmad (2010)

(untitled)
Although the concept of spirituality in the workplace has received enormous attention from contemporary researchers, very little or not sufficient research has been attempted from the religious perspective. This conceptual paper attempts to enrich the understanding of the spirituality in the workplace phenomenon from an Islamic Management perspective. In doing so, the conceptual paper attempts to study the theoretical and practical meanings of Taqwa, the characteristics of Taqwa, the two dimensions of Taqwa known as the Islamic spirituality and Islamic social responsibility, together with the mediating effect of “sabr” i.e. patience. The two dimensions of Taqwa are hypothesised to have direct positive effects on organizational performance whiles patience has a mediating effect on overall organizational performance.The literature used for this study is exclusively from the Qur’an and the Prophetic Tradition of the Prophet Muhammad (peace be upon him). Implications for future research were provided.